An experimental study targeting N-methyl-D-aspartate receptor in depression; beyond ketamine - Salim Sheikh; Pankaj Sonone; Chakar Dhar Tripathi; Veena Verma; Bushra Ahmed Karim (Annals of Psychiatry and Treatment - Peertechz Publications, 2020)
Objective: Despite the availability of vast group of drugs, treatment of depression still remains unsatisfactory. Serious adverse effects of anti-depressants lead to early withdrawal from treatment. One more important concern is the therapeutic lag of nearly 3-4 weeks. Therefore, newer targets for drugs with good safety profile, rapid onset of action and with substantial benefits in comparison to conventional therapy need to be explored. Method: 10 groups of 6 mice each were evaluated for immobility time in TST and FST. Treatment used was normal saline (control), citalopram, ketamine, glycine and combination of ketamine with glycine. Results: Significant decrease in immobility time was observed in ketamine treated mice in both models. Citalopram decreased the immobility time in both models but it was not significant in FST. Glycine treated mice showed a significant increase in immobility time in both. Ketamine and glycine combination also increased the immobility time, though, it was not significant.  Conclusion: Ketamine have an antidepressant activity of its own which could be attributed to involvement of NMDA receptors and its interaction with the monoaminergic system. On the other hand, glycine, a co-agonist of NMDA receptor elicited a depressant effect. Moreover, their combination favored towards depressant effect.